Incidence and risk factors of venous thrombotic events in patients with interstitial lung disease during hospitalization - Haishuang Sun; Min Liu; Xiaoyan Yang; Linfeng Xi; Wenqing Xu; Mei Deng; Yanhong Ren; Wanmu Xie; Huaping Dai; Chen Wang (Thrombosis Journal, 2023)
Abstract Background Studies on the incidence of venous thromboembolism (VTE) events in patients with interstitial lung disease (ILD) are limited and the results are inconsistent. The aim of this research was to investigate the incidence and risk factors of VTE in ILD during hospitalization. Materials and methods In this retrospective, cross-sectional, observational study, a total of 5009 patients diagnosed with ILD from January 2016 to March 2022 in our hospital were retrospectively included. In ILD patients, VTE including pulmonary thromboembolism (PTE) and deep vein thrombosis (DVT) were screened from the electronic medical record system. Diagnosis of PTE and DVT were performed by CT pulmonary angiography (CTPA), CTV or ultrasound. And then the incidence and risk factors of VTE in different types of ILD were assessed. Results Among 5009 patients with ILD, VTE was detected in 129 (2.6%) patients, including 15(0.3%) patients with both PTE and DVT, 34 (0.7%) patients with PTE and 80 (1.6%) patients with DVT. 85.1% of patients with APE were in the intermediate-low risk group. The incidence of VTE in Anti-Neutrophil Cytoplasmic Antibodies -associated vasculitis related ILD (ANCA-AV-ILD), hypersensitivity pneumonitis and idiopathic pulmonary fibrosis (IPF) respectively was 7.9% and 3.6% and 3.5%. In patients with connective tissue disease-associated ILD (CTD-ILD), the incidence of VTE, DVT, PTE, combined PTE and DVT respectively was 3.0%, 2.3%, 0.4% and 0.3%. Among the various risk factors, different ILD categories, age ≥ 80 years (OR 4.178, 95% CI 2.097–8.321, P < 0.001), respiratory failure (OR 2.382, 95% CI 1.533–3.702, P < 0.001) and varicose veins (OR 3.718, 95% CI 1.066–12.964, P = 0.039) were independent risk factors of VTE. The incidence of VTE in patients with ILD increased with the length of time in hospital from 2.2% (< 7 days) to 6.4% (> 21 days). Conclusion The incidence of VTE during hospitalization in ILD patients was 2.6%, with a 1.6% incidence of DVT, higher than the 0.7% incidence of PTE. Advanced age, ILD categories, respiratory failure and varicose veins as independent risk factors for the development of VTE should be closely monitored.